Health promotion behaviors and its correlation with some of the demographic factors in patients with multiple sclerosis - Dashti–Dehkordi, Alireza; Yousefi, Hojatolah; Etemadifar, Masoud; Maghsoudi, Jahangir (Advances in Nursing & Midwifery, 2017)
Abstract Background and Aim: The health promotion behaviors are effective factors in prevention of diseases. The aim of this study was to determine, the health promotion behaviors and their relationship with demographic factors in people with multiple sclerosis. Materials and Methods: This study was a descriptive cross-sectional survey assessing health-promoting behaviors among patients with multiple sclerosis. 51 patients with multiple sclerosis referred to MS clinic of Al- Zahra Hospital were randomly selected. The health-promoting behaviors were measured using HPLP-II (Health Promotion Lifestyle profile-II) and Expanded Disability Status Scale (EDSS). Data were analyzed by independent t-test, Pearson Correlation, Spearman correlation and One-Way ANOVA. Findings: The overall health-promoting behaviors’ profile had a mean ± SD of 119.6±12. The highest mean in the sub-scales was for “spiritual growth” (22.8±3/8) and the lowest was for “physical activity” (15.3±3.52). The results indicated that there was not a significant difference between two genders. Pearson’s correlation indicated a negative relationship between Expanded Disability Status Scale with mean of overall health-promoting behaviors’ profile. There were also significant correlations between the levels of education with mean of overall health-promoting behaviors’ profile. Conclusion: Regarding the situation of health-promoting behaviors, especially in physical activity sub-scale, providing programs to improve health promotion behaviors in people with multiple sclerosis are recommended. Keywords: Health Behavior; Multiple sclerosis; Demographic Factors